Representasi Komunikasi Keluarga dalam Film “Ngeri-Ngeri Sedap” : (Analisis Semiotika Roland Barthes dalam Film “Ngeri-Ngeri Sedap) - Naufal Daffa Ramadhan Desiantoro; Oji Kurniadi (UNISBA Press, 2024)
Abstract. The impact provided by the family is very large and important in the development of human life, one example is that family communication creates a big picture in their children when they grow up. The place where humans can learn to communicate for the first time is when communicating with family. The impact given by the family is very large and important in the development of human life, one example is that family communication creates a big picture of their children when they grow up. Movies with family themes are one of the media in modern mass communication. In this research, the movie